The Relationship between Nutritional Status and Intelligence Level of Elementary School Children in Benu-Benua Village, Kendari City - Usnia, Usnia; Sunarsih, Sunarsih; Banudi, La (Waluya The International Science of Health Journal, 2023)
Introduction: Kendari city as the provincial capital with the largest number of health facilities and logistical access compared to other cities in Southeast Sulawesi still finds cases of malnutrition around 5%. The percentage of undernourished, at the age of 0-59 months, the highest was recorded at the Benu-benua health center, Benu-benua village at 2.15%, far above the Kendari city average of 0.72%. This nutritional status is thought to be related to the level of intelligence of children in the area. Methods: The type of research that will be conducted is quantitative research with a cross-sectional design. Population of this study is 251 students and the number of samples is 108, the sampling method is stratified random sampling, the data is tested with the Kruskal Wallis test after the data obtained are not normally distributed. Result: The results of this study on the current nutritional status showed a P Value of 0.017 < 0.05 and the previous nutritional status showed a P Value of 0.026 < 0.5, while the social status showed a P Value of 0.139 > 0.05. Conclusion:The conclusion of this study is that there is a relationship between current nutritional status and previous nutritional status with students' IQ scores and there is no relationship between socioeconomic status and students' IQ scores.